Treatment of clinically amyopathic dermatomyositis in adults: a systematic review. (1st December 2018) - Callander, J.; Robson, Y.; Ingram, J.; Piguet, V.
Summary: Clinically amyopathic dermatomyositis (CADM) affects a subset of 5–20% of patients with dermatomyositis and is defined as the presence of cutaneous features of dermatomyositis without clinical muscle weakness for ≥ 6 months. There is no consensus on first‐line treatment for CADM and whether treatment should differ from treatment of classic dermatomyositis with muscle weakness. We carried out a systematic review of published literature about treatment of adult patients with CADM, via the Embase, Medline, CINAHL and ClinicalTrials.gov databases on 17 February 2015. The aim was to establish which treatments have been used for adult‐onset CADM and what evidence is available regarding the efficacy of these treatments including topical treatments, dapsone, antimalarials, intravenous immunoglobulin (IVIG), nonsteroidal oral immunosuppressants and biological therapies. Eighteen cases series and 42 case reports were found. These provided data on 153 adult patients who met the inclusion criteria. No randomized controlled trials or robust observational studies were found. The majority of patients (60%) had tried more than one treatment due to side‐effects or lack of efficacy. Antimalarial agents were the most commonly used treatment type. In the majority of patients (55%), antimalarial treatments were discontinued due to lack of improvement or inability to wean concomitant steroids. IVIG was the treatment that led to improvement or remission in the greatest proportion of patients. Further robust, high‐quality studies are needed to assess treatment efficacy in CADM without bias.